Risk factors of nonalcoholic fatty liver disease in lean body mass population: A systematic review and meta‐analysis - Shahinul Alam (Wiley, 2021)
Abstract The pathophysiology and risk factors of nonalcoholic fatty liver disease (NAFLD) among lean patients is poorly understood and therefore investigated. We performed a meta‐analysis of observational studies. Of 1175 articles found through searching from Medline/PubMed, Banglajol, and Google Scholar by two independent investigators, 22 were selected. Data from lean (n = 6768) and obese (n = 9253) patients with NAFLD were analyzed; lean (n = 43 398) and obese (n = 9619) subjects without NAFLD served as controls. Age, body mass index, waist circumference, systolic blood pressure, and diastolic blood pressure (DBP) had significantly higher estimates in lean NAFLD patients than in lean non‐NAFLD controls. Fasting blood sugar [MD(mean difference) 5.17 mg/dl, 95% CI(confidence interval) 4.14–6.16], HbA1c [MD 0.29%, 95% CI 0.11–0.48], and insulin resistance [HOMA‐IR] [MD 0.49 U, 95% CI 0.29–0.68]) were higher in lean NAFLD patients than in lean non‐NAFLD controls. All components of the lipid profile were raised significantly in the former group except high‐density lipoprotein. An increased uric acid (UA) level was found to be associated with the presence of NAFLD among lean. Cardio‐metabolic profiles of nonlean NAFLD patients significantly differs from the counter group. However, the magnitude of the difference of lipid and glycemic profile barely reached statistical significance when subjects were grouped according to lean and nonlean NAFLD. But DBP (slope: 0.19, P < 0.037), HOMA‐IR (slope: 0.58, P < 0.001), and UA (slope: 0.36, P = 0.022) were significantly higher if NAFLD was present compared to that of non‐NAFLD group. Lean and nonlean NAFLD patients are metabolically similar and share common risk factors.